Formation of the structure and characteristics of rolled wire at cooling by high-speed air streams - V. V. Filippov; V. A. Tishchenko; A. Ju. Borisenko; G. V. Levchenko; A. A. Gorbanev (Литьë и металлургия)
The experimental investigations of the structure and characteristics of the rolled wire cooled by air streams of different rates, imitating the conditions of the second stage of cooling of the modern high-speed rolled mills, are carried out. The results of investigations showed the necessity to increase the maximum possible rate of air stream at the second stage of cooling in comparison with the available at the many mills cooling rate.